THE INFLUENCE OF QUALITY AND INNOVATION ON PURCHASING DECISIONS THROUGH COMPETITIVE ADVANTAGE USING DIGITAL PAYMENT - Alfrianda, Thomas Eka; Mulyono, Mulyono; Rianta, Muhamad; Hasibuan, Mhd. Farhan Yazid (ULTIMA Management, 2024)
Abstract- Financial technology, or fintech, aims to make it easier for people to access digital-based financial products, facilitate transactions, and increase financial literacy. Digital payment is one of the fintech products used by the public as a means of payment. Digital payment can be used as a transaction tool through merchants and various e-commerce and directly through the application. The study aimed to determine the effect of innovation and product quality on competitive advantage and its impact on purchasing decisions using digital payments. The research method used in this study uses quantitative methods and survey implementation. The population of this study includes respondents who are users of digital payment products, namely OVO, with a sampling technique, namely simple random sampling. The number of samples used in the study was 100 respondents. The analysis technique used is Structural Equation Modeling (SEM) with the help of SmartPLS software. The results showed that there is a positive and significant influence between product quality variables on the company's competitive advantage, and there is a positive and significant influence between product innovation variables on the company's competitive advantage. The product quality variable has a positive influence on purchasing decisions. Product innovation has a positive and significant effect on purchasing decisions, and competitive advantage variables have a positive and significant effect on consumer purchasing decisions. Keywords: Competitive advantage; Digital payment; Innovation; Purchase decision; Quality.